Citizen Science: Eine Chance für wissenschaftliche Bibliotheken - Wiederkehr, Stefan (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2021)
Recently, there has been an increasing interest in Citizen Science, understood as the collaboration of professional and volunteer researchers in the entire research cycle from the development of scientific questions to the collection, analysis and interpretation of data. Based on the practical experiences of the Zentralbibliothek Zürich, this direction-setting article identifies three opportunities, which foster Citizen Science in academic libraries. First, the regular customers are potential Citizen Scientists with whom the libraries already have well-established contacts. Second, the infrastructures guarantee the sustainability of the results of Citizen Science projects. Third, the libraries’ digitized holdings make it possible to put new kinds of questions to well-known material in Citizen Science projects.With respect to academic libraries – especially those which function both as a university library and as a state, regional or city library – Citizen Science can strengthen their position as mediators between science and the public, helping to shape new forms of participation and supporting the process of knowledge production.
Keywords: Citizen Science; Academic libraries